Analisis Pengaruh Modal, Produktivitas, Teknologi Dan Harga Jual Terhadap Pendapatan Nelayan Di Kecamatan Bone Pantai - Sri Relin Kacong; Syarwani Canon; Irawati Abdul (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2026)
The results of the study show that: (1) capital has a positive and significant effect on fishermen’s income. This indicates that any increase in capital will lead to an increase in fishermen’s income in Bone Pantai District, as capital is the main production factor supporting all operational activities, including the provision of fishing gear, fuel, boat maintenance, and fishing logistics. (2) Productivity has a positive and significant effect on fishermen’s income. This means that higher productivity increases fishermen’s income, as productivity reflects the ability of fishermen to produce a greater quantity or higher-value catch in a more efficient use of time and cost. (3) Technology has a positive and significant effect on fishermen’s income. This implies that improvements in technology contribute to higher income, since technology plays an important role in enhancing the efficiency and effectiveness of fishing operations. (4) Selling price has a positive and significant effect on fishermen’s income. This means that an increase in the selling price will increase fishermen’s income, as higher prices provide direct economic benefits, especially in areas such as Bone Pantai where most fishermen still rely on traditional marketing systems. (5) Capital, productivity, technology, and selling price simultaneously have a significant effect on fishermen’s income in Bone Pantai District. This indicates that simultaneous improvements in these four variables strengthen business capacity, increase the value of fish catch, improve operational efficiency and product quality, and directly add value to fishermen’s income.